Determinants of Tourist Satisfaction in Silokek Geopark Tourism - Reni Yuliviona; Afrizal Afrizal; Nusrat Jahan (Jurnal Manajemen Universitas Bung Hatta, 2023)
This study aims to prove the effect of location, promotion, and facilities on tourist satisfaction. This study uses data collection methods by distributing questionnaires. The respondents of this study are the tourists who visited the Silokek Geopark tourism located in West Sumatra, Indonesia, with a total of 80 respondents. The data analysis method in this research is SEM-PLS. The hypotheses in this study were tested using analytical techniques, including Measurement Model Assessment, Descriptive Analysis, R Square, Q Square and Structural Model Assessment. From the test results, it can be concluded that the location and promotion have no effect on satisfaction at the Silokek Geopark tourist attraction, and facilities positively affect satisfaction at the Silokek Geopark tourist attraction.